Mini-Review on Bioinspired Superwetting Microlens Array and Compound Eye - Yong, Jiale; Bian, Hao; Yang, Qing; Hou, Xun; Chen, Feng (Frontiers in Chemistry, 2020)
Microlens arrays (MLAs) and MLA-based artificial compound eyes (ACEs) are the important miniaturized optical components in modern micro-optical systems. However, their optical performance will seriously decline once they are wetted by water droplets (such as fog, dew, and rain droplets) or are polluted by contaminations in a humid environment. In this mini-review, we summarize the research works related to the fabrication of superwetting MLAs and ACEs and show how to integrate superhydrophobic and superoleophobic microstructures with an MLA. The fabrication strategy can be split into two categories. One is the hybrid pattern composed of the MLA domain and the superwetting domain. Another is the direct formation of superwetting nanostructures on the surface of the microlenses. The superhydrophobicity or superoleophobicity endows the MLAs and ACEs with liquid repellence and self-cleaning function besides excellent optical performance. We believe that the superwetting MLAs and ACEs will have significant applications in various optical systems that are often used in the humid or liquid environment.